2020
DOI: 10.3390/en13143699
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on a Bio-Composite Material as Acoustic Absorber and Thermal Insulation

Abstract: In order to limit the anthropic emissions of CO2, research is currently investigating new materials for the building sector. The main purpose is the reduction in the embodied energy consumption, especially in the residential sector, and consequently the limitation of the direct and indirect utilization of fossil fuels, for the indoor heating, cooling, and ventilation services. Indeed, the residential sector is affected by a high energy demand, thus the choice of improved materials is fundamental to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Indeed, Brzyski et al [ 54 ] found that for the lightest experimented mixtures, the compressive strength was below 1 MPa, and the thermal conductivity below 0.1 W/(m·K), making them better than autoclaved aerated concretes. The study proposed by Curto et al [ 55 ] has shown that the increase in the percentage of hemp shives in a mixture of lime and water decreases the thermal conductivity and increases the sound absorption values. Pochwała et al [ 56 ] found for a hemp-lime composite that the thermal conductivity ranged from 0.038–0.055 W/(m·K), depending on how much the shiv was compacted and what mixing method was applied.…”
Section: State-of-artmentioning
confidence: 99%
“…Indeed, Brzyski et al [ 54 ] found that for the lightest experimented mixtures, the compressive strength was below 1 MPa, and the thermal conductivity below 0.1 W/(m·K), making them better than autoclaved aerated concretes. The study proposed by Curto et al [ 55 ] has shown that the increase in the percentage of hemp shives in a mixture of lime and water decreases the thermal conductivity and increases the sound absorption values. Pochwała et al [ 56 ] found for a hemp-lime composite that the thermal conductivity ranged from 0.038–0.055 W/(m·K), depending on how much the shiv was compacted and what mixing method was applied.…”
Section: State-of-artmentioning
confidence: 99%
“…The thermal conductivity of biobased composites, which represents an essential characteristic of the insulation of buildings, was studied by Pochwała et al [ 6 ]. The same problem was analyzed by [ 7 ], who studied biocomposites made of natural lime and hemp. The physical and mechanical properties of biocomposites, hemp, and lime were determined by Brzyski et al The thermal conductivity test was carried out on samples with dimensions of 250 × 250 × 50 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Curto et al [ 7 ] studied the thermal and acoustic characteristics of materials obtained by mixing natural lime, water, and hemp. Their investigations were conducted on samples of defined size and appropriate shapes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still very few publications that collect data and then can be used to standardize regulations for application of materials such as hemp shives [26], straw [27], or light clay [15]. Meanwhile, these materials show a very low impact on the natural environment, and in the case of hemp shives and straw, the CO 2 emission balance in their production process is negative (due to a large quantity of CO 2 absorbed during the growth of these plants) [28].…”
Section: Introductionmentioning
confidence: 99%